Lookup: Interactive Travel Blog Website - Mohamed Rawi, Mohd Hakim; Ab Ghani, Zuriani (Journal of Computing Technologies and Creative Content, 2021)
This research was created to address the needs of the Final Year Project before UniKL MIIT's graduation in June 2021. The aim of this thesis is to assess students' comprehension of the subjects they learned during their time at UniKL MIIT. Thus, the researcher decides to develop “Lookup: An Interactive Travel Blog Website”. This project aims to create a local website that is only connected to Malaysian tourism destinations and provides helpful information for users with some immersive multimedia elements as printed outlets become more costly and unavailable. Furthermore, this website will undoubtedly support small businesses by promoting locations, food, and community. The Waterfall Model was used as the research model for this project. According to the results of a poll, the majority of respondents believe that the website is useful in exposing them to new locations, food, and culture in Malaysia, and that it can be used as a forum for sharing knowledge.